How Uncertainty Influences Lay People’s Attitudes and Risk Perceptions Concerning Predictive Genetic Testing and Risk Communication - Wöhlke, Sabine; Schaper, Manuel; Schicktanz, Silke (Frontiers in Genetics, 2019)
The interpretation of genetic information in clinical settings raises moral issues about adequate risk communication and individual responsibility about one’s health behavior. However, it is not well-known what role numeric probabilities and/or the conception of disease and genetics play in the lay understanding of predictive genetic diagnostics. This is an important question because lay understanding of genetic risk information might have particular implications for self-responsibility of the patients. Aim: Analysis of lay attitudes and risk perceptions of German lay people on genetic testing with a special focus on how they deal with the numerical information. Methods: We conducted and analyzed seven focus group discussions (FG) with lay people (n= 43). Results: Our participants showed a positive attitude towards predictive genetic testing. We identified four main topics: 1) Anumeric risk instead of statistical information; 2) Treatment options as a factor for risk evaluation; 3) Epistemic and aleatory uncertainty as moral criticism; 4) Ambivalence as a sign of uncertainty. Conclusions: For lay people, risk information, including the statistical numeric part, is perceived as highly normatively charged, often as an emotionally significant threat. It seems necessary to provide lay people with a deeper understanding of risk information and of the limitations of genetic knowledge with respect to one’s own health responsibility.